1999
DOI: 10.1152/jn.1999.81.3.1412
|View full text |Cite
|
Sign up to set email alerts
|

Action Potentials in the Dendrites of Retinal Ganglion Cells

Abstract: The somas and dendrites of intact retinal ganglion cells were exposed by enzymatic removal of the overlying endfeet of the Müller glia. Simultaneous whole cell patch recordings were made from a ganglion cell's dendrite and the cell's soma. When a dendrite was stimulated with depolarizing current, impulses often propagated to the soma, where they appeared as a mixture of small depolarizations and action potentials. When the soma was stimulated, action potentials always propagated back through the dendrite. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 24 publications
7
53
0
Order By: Relevance
“…ON and OFF cells appear to express similar intrinsic properties (O'Brien et al, 2002), but we cannot completely rule out their contribution to differences in ON and OFF sensitivities (Velte and Masland, 1999;Chen and Diamond, 2002), Different inhibitory mechanisms for ON and OFF Previously, we observed that ON and OFF cells have different mechanisms for inhibition; an ON cell receives indirect inhibition (i.e., reduced excitation), reducing a conductance that reverses positive to V rest , whereas an OFF cell receives direct inhibition, increasing a conductance that reverses negative to V rest (Demb et al, 2001a,b). However, these previous experiments were performed either under a pharmacological condition in which spiking amacrine cells were blocked or else with relatively complex motion stimuli.…”
Section: Discussionmentioning
confidence: 90%
“…ON and OFF cells appear to express similar intrinsic properties (O'Brien et al, 2002), but we cannot completely rule out their contribution to differences in ON and OFF sensitivities (Velte and Masland, 1999;Chen and Diamond, 2002), Different inhibitory mechanisms for ON and OFF Previously, we observed that ON and OFF cells have different mechanisms for inhibition; an ON cell receives indirect inhibition (i.e., reduced excitation), reducing a conductance that reverses positive to V rest , whereas an OFF cell receives direct inhibition, increasing a conductance that reverses negative to V rest (Demb et al, 2001a,b). However, these previous experiments were performed either under a pharmacological condition in which spiking amacrine cells were blocked or else with relatively complex motion stimuli.…”
Section: Discussionmentioning
confidence: 90%
“…This optimization for speed, however, would decrease the alpha cell's relative sensitivity to an equivalent synaptic input to other RGC types, yet they would appear to be among the most sensitive cells to visual contrast (Kaplan and Shapley 1986). This apparent paradox implies that A2/alpha cells either have increased synaptic input relative to other RGC types or possibly also employ active dendritic conductances to enhance their sensitivity (Dhingra et al 2005;Velte and Masland 1999). Whether retinal cells receive the same number of synapses per linear micrometer of dendrite is a matter of some disagreement in the literature (Eriköz et al 2008;Jakobs et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…At one level, it seems that the amacrine and ganglion cell models are not very different. In the ganglion cell model, Na ϩ channels were also required in the dendrites and evidence of dendritic action potentials has been reported (Velte and Masland 1999). Voltage-gated Na ϩ channels in the ganglion cell model were sufficient in density to generate a back-propagated impulse (Fohlmeister and Miller 1997b) but not a forward-propagated impulse as appears to be present in the dendrites of ON-OFF amacrine cells.…”
Section: Amacrine Versus Ganglion Cell Modelmentioning
confidence: 98%